Under the gun and the archive: examining police lethality and legitimacy in Greater Curitiba (2017-2018) (Global Journal of Human-Social Science, 2023)
The Brazilian police are one of the ones that kill the most in the world. In 2022, Brazilian police killed around 6 thousand people. What does the State do in the face of this? This article seeks to examine exactly that answer. Based on the analysis of 37 completed court cases (2017)(2018) in the city of Curitiba in the State of Paraná/Brazil, we analyzed the police discourse on police lethality and how the judiciary interprets it. The Judiciary almost always archives the case and there is no punishment. Based on this information, we seek to understand the relationship between police lethality and repression in the Brazilian neoliberal State -the current state configuration.
Keywords: RPL; neoliberal state; greater curitiba; legal discourse and legitimation